2016
DOI: 10.1016/j.gene.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CXCL6 and BBS5 that may be glaucoma relevant genes is regulated by PITX2

Abstract: The transcription factor PITX2 is implicated in glaucoma pathology. In an earlier study we had used microarray analysis to identify genes in the trabecular meshwork (TM) that are affected by knock down of PITX2. Here, those studies were pursued to identify genes that are direct targets of PITX2 and that may be relevant to glaucoma. Initially, bioinformatics tools were used to select among the genes that had been affected by PITX2 knock down those that have PITX2 binding sites and that may be involved in glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 90 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…Further, we speculate that PITX2 may be involved in anti-oxidant or regenerative responses in the appendix. In the heart PITX2 promotes regeneration after injury through anti-oxidant response (Tao et al 2016), and in the eye it may mediate the response to oxidative stress (Paylakhi et al 2011; Strungaru et al 2011), where it targets a pro-inflammatory cytokine (Moazzeni et al 2016) and a gene encoding response to oxidative stress (Strungaru et al 2011). PITX2 also promotes skeletal muscle regeneration through its repression of miR-31 (Vallejo et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we speculate that PITX2 may be involved in anti-oxidant or regenerative responses in the appendix. In the heart PITX2 promotes regeneration after injury through anti-oxidant response (Tao et al 2016), and in the eye it may mediate the response to oxidative stress (Paylakhi et al 2011; Strungaru et al 2011), where it targets a pro-inflammatory cytokine (Moazzeni et al 2016) and a gene encoding response to oxidative stress (Strungaru et al 2011). PITX2 also promotes skeletal muscle regeneration through its repression of miR-31 (Vallejo et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Bardet-Biedl syndrome 5 (BBS5) has also been found to be localized in trabecular meshwork cilia. Microarray analysis and dual luciferase assays confirmed that BBS5 is regulated by the transcription factor paired like homeodomain 2 (PITX2), and the absence of PITX2 not only activates pro-inflammatory cytokines, but also reduces BBS5 to damage cilia ( Moazzeni et al., 2016 ).…”
Section: Primary Cilia Of Ocular Tissuesmentioning
confidence: 98%
“…PITX2 regulates expression of additional potentially glaucoma‐relevant genes, including CXCL6 , BBS5 , and ALDH1A1 (Moazzeni, Akbari, Yazdani, & Elahi, 2016; Paylakhi et al, 2011; Paylakhi et al, 2013). CXCL6 has immune functions (Moazzeni et al, 2016; Paylakhi et al, 2011; Paylakhi et al, 2013).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…PITX2 regulates expression of additional potentially glaucoma‐relevant genes, including CXCL6 , BBS5 , and ALDH1A1 (Moazzeni, Akbari, Yazdani, & Elahi, 2016; Paylakhi et al, 2011; Paylakhi et al, 2013). CXCL6 has immune functions (Moazzeni et al, 2016; Paylakhi et al, 2011; Paylakhi et al, 2013). BBS5 may affect functions of ciliary bodies which are the source of aqueous humor in the anterior chamber (Coca‐Prados & Escribano, 2007; Kiel, Hollingsworth, Rao, Chen, & Reitsamer, 2011; Nachury et al, 2007).…”
Section: Transcription Factorsmentioning
confidence: 99%